2020
DOI: 10.1017/s1368980020003663
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium and potassium intake: knowledge, attitude and behaviour towards dietary salt intake among adults in Addis Ababa, Ethiopia

Abstract: Objective: The present study aimed to estimate the consumption of Na and K and to assess salt-related knowledge, attitude and behaviour among adults in Addis Ababa, Ethiopia. Design: A community-based cross-sectional study was conducted. Estimates of Na and K intake were made using repeated multiple-pass 24-h dietary recall as well as using random urine. The usual intake of Na and K from the 24-h dietary recall was determined using the National Cancer Institute methodology. Estimated 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…However, only a small proportion reported taking regular actions to control salt (10% and 2.6%), and their actual salt consumption was much higher than the recommended level of ≤5 g/day (98% of the participants consumed ≥5 g salt/day in the present study). Our results of participants’ levels of knowledge and attitudes are comparable to those reported from studies in India [ 22 ], China [ 23 ], Malaysia [ 24 ], the United Arab Emirates [ 25 ], Australia [ 26 ], Samoa [ 27 ], Ethiopia [ 28 ], and the five sentinel countries of the Americas [ 29 ]; however, the proportion of our participants taking regular actions to control their salt intake was comparatively lower compared with those studies.…”
Section: Discussionsupporting
confidence: 86%
“…However, only a small proportion reported taking regular actions to control salt (10% and 2.6%), and their actual salt consumption was much higher than the recommended level of ≤5 g/day (98% of the participants consumed ≥5 g salt/day in the present study). Our results of participants’ levels of knowledge and attitudes are comparable to those reported from studies in India [ 22 ], China [ 23 ], Malaysia [ 24 ], the United Arab Emirates [ 25 ], Australia [ 26 ], Samoa [ 27 ], Ethiopia [ 28 ], and the five sentinel countries of the Americas [ 29 ]; however, the proportion of our participants taking regular actions to control their salt intake was comparatively lower compared with those studies.…”
Section: Discussionsupporting
confidence: 86%
“…[20][21][22] Our study provides contemporary evidence of the risk associated with high serum potassium levels in the Chinese general population, which has marked differences in lifestyle, particularly the dietary pattern related to potassium levels, compared with Western populations. [23][24][25] To the best of our knowledge, only two previous studies have evaluated the association of serum potassium levels with incident CVD events in the general population. 7,10 Neither of these reports which were based on the Framingham Offspring Study and the Multi-Ethnic Study of Atherosclerosis and the Cardiovascular Health Study showed a significant association between serum potassium levels and the incidence of CVD in the US population.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese Australian group had significantly lower salt-related knowledge than their counterparts in China. Compared with other ethnic populations, our participants had a higher awareness of the daily recommended salt intake than study participants in Ethiopia and Northern India, where only 1.8% and 5% of participants respectively were aware of the daily recommended salt intake [ 60 , 61 ]. However, over 87% of the participants in the Ethiopian study were aware of the increased risk of hypertension with a high salt intake.…”
Section: Discussionmentioning
confidence: 76%